Chad : Request for Disbursement under the Rapid Credit Facility and Cancellation of the Extended Credit Facility Arrangement-Press Release; Staff Report; and Statement by the Executive Director for Chad. (IMF Staff Country Reports; Country Report ;, 2020)
Chad's economy has been severely impacted by the twin Covid-19 pandemic and terms of trade shocks. A national lockdown to contain the spread of the virus, disruptions in supply chains, and a drop in international oil prices are curtailing economic activity and weakening the outlook. While the authorities' policy response has been timely and proactive, the economic shock and containment policies are triggering a severe recession, resulting in significant social costs and urgent balance of payment and budget financing needs. These are estimated at 7.0 percent of non-oil GDP compared to 4.6 percent in IMF Country Report No. 20/134. The pandemic is unfolding in a context of rising regional and domestic insecurity and an already weak health care system, which are exacerbating Chad's vulnerabilities.